ROLLING STOCK DISTRIBUTION FOR PARKING BETWEEN PUBLIC AND NON-PUBLIC RAILWAY TRACKS - Yelovoy, I. A.; Potylkin, Y. N. (Science and Transport Progress, 2018)
Purpose. The tasks of selecting the optimal modes of mutual operation of the public and non-public tracks are particularly relevant in the context of increasing the share of private cars. Therefore, the aim of this paper is to develop an approach to the justification of the choice of the interaction mode between mainline and industrial railway transport from the position of cars distribution sent to parking between public and non-public railway tracks. Me-thodology. To achieve this purpose, authors used the methods of scientific analysis and synthesis, graph theory, as well as experimental and statistical methods of modeling. Findings. Dependence of the required capacity of railway tracks was obtained. It takes into account the share of private cars in the general park arriving at places of non-public use. We proposed a scheme for choosing the place of location of cars to justify the choice of the mode of interaction between the main and industrial railway transport, taking into account the available track equipment and the expediency of its further development. Originality. The task in this formulation has not been solved to date, which determines the relevance and originality of research in this direction. The resulting formula for determining the required capacity of railway tracks takes into account the influence of the random nature of servicing of private conveyances at places of non-public use, as well as the share of carriages of consignors, consignees in the general park. We proposed the method for choosing the location of private rolling stock, used to justify the choice of the mode of interaction between the main and industrial railway transport, taking into account the available track equipment and the expediency of its further development. A distinctive feature of the presented method is the consideration of the interests of the cargo owner, as a party most interested in the effective mutual work of public and non-public railway tracks. Practical value. Based on the results of the study recommendations can be received on the choice of the mode of interaction between the main and industrial railway transport in the part of the cars distribution sent to parking between public and non-public railway tracks. This will reduce the costs of cargo owners by minimizing economic and time losses and, as a result, make railroad services more attractive to customers, which will lead to an increase in its competitiveness in the transport services market.